ANALISIS KINERJA BETON PERMEABEL DENGAN PENAMBAHAN COCOPEAT DAN IJUK TERHADAP KUAT TEKAN UNTUK PENINGKATAN EFEKTIVITAS DRAINASE - Syahwanti, Hezliana; Widodo, Muji Listyo; Irvhaneil (Politeknik Negeri Semarang, 2025)
This research is driven by the increasing need for environmentally friendlyconstruction materials to address sand scarcity and flooding issues in Pontianak. Thestudy aims to analyze the performance of permeable concrete by incorporatingcoconut coir powder (cocopeat) and sugar palm fiber (ijuk) as partial substitutes forsand, with the goal of enhancing drainage effectiveness. The methodology involved alaboratory experiment where cylindrical concrete test specimens were created with amixture variation of 1% cocopeat and 1% ijuk by weight of sand. Subsequently,compressive strength tests were conducted at concrete ages of 7, 14, 21, and 28 days.The test results indicate a trend of increasing strength as the concrete ages, with theaverage compressive strength of the mixed concrete reaching 10.6 MPa at 28 days.Although this value is lower than that of conventional concrete, which averages 13.0MPa, the addition of cocopeat was proven to increase the porosity essential fordrainage functions. Meanwhile, the sugar palm fiber played a positive role incontrolling micro-cracks. Therefore, this permeable concrete shows significantpotential as a sustainable material for non-structural applications such as sidewalks,pedestrian paths, and light-load parking areas where water absorption is a priority.